Pengembangan Media Pembelajaran Video Animasi Sebagai Daya Dukung Kemampuan Representasi Matematis Siswa - Khayroiyah, Siti; Sukmawarti, Sukmawarti; Hidayat, Hidayat; Kadir, Dalimawaty (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Based on the results of observations conducted by conducting a mathematical representation ability test on students of SMP IT Al-Fauzi, researchers obtained data that students' visual mathematical representation abilities were classified as moderate, and mathematical representation abilities on verbal representation indicators and mathematical expression representation of students were classified as low. The rapid development of information technology at this time cannot be separated from its influence on the world of education. Global demands require the world of education to adjust learning to technological developments, with the aim of improving the quality of education, as well as to improve teacher performance in order to be able to compete in the global world, in the current era of technological development, learning media has an important role in conveying messages from the sender to the recipient, in this case the existence of learning media has an important role in conveying material by educators to students, with the existence of learning media will make the learning atmosphere more effective and can overcome boredom in learning in class. One of the learning media is audio-visual media, saying that there is a problem regarding the lack of teacher knowledge regarding the creation and use of learning media. Therefore, teachers are expected to be able to equip themselves with insight and skills in designing learning media, because without sufficient provisions, teachers cannot improve the quality of their learning. The steps of this 4-D development model consist of 4 stages: the define stage, design, develop and implement. This research was conducted in the odd semester, the research was conducted at SDIT AL-Fauzi Medan. The Technology Readiness Level (TKT) of this study is a proof of concept related to the Development of Animated Video Learning Media as a supporting force for Students' Mathematical Representation Abilities which produces RPP and measuring tools to measure students' representation abilities and learning media so that they can influence learning outcomes and can be utilized in the learning and teaching process in the world of education.